2018
DOI: 10.1590/s0100-83582018360100051
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Ability of Santa-Maria (Parthenium hysterophorus L.) with Spring Maize

Abstract: In recent decades, allelopathy has gained considerable attention in sustainable agricultural systems. In the current situation, an attempt has been made to investigate the optimal competition period for weed control in maize. Experiments were designed in randomized complete block design and Parthenium hysterophorus was naturally infested in experimental plots during the spring season 2014 to determine the critical competition period for weed control in maize. The relations between grain yield and different com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…This is due to longer persistence of the chemical and the high suppression, avoiding regrowth and uprooting of the weed by mechanical management system up to harvest. This result supports the finding of Anafjeh and Chaab (2012) and Rehman, Qamar, Farooq, Qamar, and Hassan (2018) who also found that the lower number of cobs with increased weed competition.…”
Section: Resultssupporting
confidence: 90%
“…This is due to longer persistence of the chemical and the high suppression, avoiding regrowth and uprooting of the weed by mechanical management system up to harvest. This result supports the finding of Anafjeh and Chaab (2012) and Rehman, Qamar, Farooq, Qamar, and Hassan (2018) who also found that the lower number of cobs with increased weed competition.…”
Section: Resultssupporting
confidence: 90%
“…This weed exhibits a high potential for competition with crops. Corn competition with Parthenium hysterophorus reduced the number of plants per meter, the height and the grain yield from 13.43 m -2 to 8.10 m -2 ; from 228.10 cm to 176.33 cm; and 22.69 ton ha -1 to 13.25 ton ha -1 , respectively when in competition for 105 days after emergence (Rehman et al, 2018). When in competition with Ambrosia artemisiifolia L., soybean presented grain productivity of 4422 kg ha -1 , but when free of competition the productivity was 5177 kg ha -1 (Barnes et al, 2018).…”
Section: _______________________________________________mentioning
confidence: 95%
“…The species Parthenium hysterophorus shows allelopathic potential with soybean (Shehzad et al, 2016), and Ambrosia artemisiifolia L. in corn (Bonea et al, 2018). As a weed, common ragweed has already been studied in soybean (Barnes et al, 2018;Coble et al, 1981;Hall et al, 2021), corn (Rehman et al, 2018), and wheat (Brighenti et al, 1994).…”
Section: _______________________________________________mentioning
confidence: 99%
“…Weeds are one of the main biotic constraints limiting common bean productivity and production. They limit the resources required for crop growth, resulting in reduced crop growth and, ultimately, affecting the crop yield and yield components through competition (Karimmojeni et al, 2021; Rehman et al., 2020; Safdar et al., 2015). The susceptibility of cultivated plants to weed competition varies according to weed density, duration of the competition, and competitive ability of weed species (Eslami et al., 2006; Kaur et al., 2017; Westbrook et al, 2021).…”
Section: Introductionmentioning
confidence: 99%